Heat transfer effects on carbon nanotubes suspended nanofluid flow in a channel with non-parallel walls under the effect of velocity slip boundary condition: a numerical study. Issue 1 (January 2017) - Khan, Umar; Ahmed, Naveed; Mohyud-Din, Syed
Abstract The present article is dedicated to analyze the flow and heat transfer of carbon nanotube (CNT)-based nanofluids under the effects of velocity slip in a channel with non-parallel walls. Water is taken as a base fluid, and two forms of CNTs are used to perform the analysis, namely the single- and multi-walled carbon nanotubes (SWCNTs and MWCNTs, respectively). Both the cases of narrowing and widening channel are discussed. The equations governing the flow are obtained by using an appropriate similarity transform. Numerical solution is obtained by using a well-known algorithm called Runge–Kutta–Fehlberg method. The influence of involved parameters on dimensionless velocity and temperature profiles is displayed graphically coupled with comprehensive discussions. Also, to verify the numerical results, a comparative analysis is carried out that ensures the authenticity of the results. Variation of skin friction coefficient and the rate of heat transfer at the walls are also performed. Some already existing solutions of the particular cases of the same problem are also verified as the special cases of the solutions obtained here.